Alignment and representation in computer science: an analysis of picture books and graphic novels for K-8 students. Issue 1 (2nd January 2021) - Haroldson, Rachelle; Ballard, Dave
ABSTRACT: Background and Content: Many children's books related to computer science have been published in the last five years, creating opportunities to integrate these texts into the classroom. Objective: Determine where the children's books support an inclusive computing culture by representing people with diverse intersectional identities engaging in the computer science practices from the K-12 Computer Science Framework. Method: We analyzed 45 picture books and graphic novels published between 2015 and 2019 targeted at K-8 students. We compiled evidence of the seven computer science practices and representation of diverse characters. Findings: Three or four practices appear in 64% of the books. The characters that engage in computing in the books are 56% female and 38% people of color. The books offer few examples of nonfictional people of color engaged in computer science, with no representation of adult males of color.